Pengembangan Model Pemilihan Green Supplier di Kawasan Industri Cikarang - Filson Maratur Sidjabat; Johan Krisnanto Runtuk (President University, 2019)
Nowadays, innovation and improvement in the industrial and logistic sector are significantly increasing sustainability issues and awareness. The concept of green supply chain focuses on the supply chain management that aims to reduce the environmental impacts, increasing the natural and ecological efficiency. The companies that are willing to accelerate their environmental performances will enhance competitive advantage that will bring income and market share enhancement, also a more positive corporate image. From the literature study, several green supplier criteria were identified and then be selected and categorized by interviewing the experts. From those results, ten criteria been developed in the model by using MCDM methods, which are DEMATEL and ANP. There are five respondents as experts in the environmental engineering field and industrial estate management, who know best the condition in Cikarang Industrial Estate. Five top criteria that have the highest weight number are Environmental management system (EMS), PROPER assessment from KLHK Indonesia (PROPER), Pollution prevention and control (PLC), Energy management/efficiency (EM), and Green design or R&D (GD).